A facile strategy for modifying boron nitride and enhancing its effect on the thermal conductivity of polypropylene/polystyrene blends. Issue 56 (17th September 2018) - Jiang, Xueliang; Ma, Pengfei; You, Feng; Yao, Chu; Yao, Junlong; Liu, Fangjun
Abstract : Selective localization of BN in the polystyrene phase by in situ polymerization of styrene can enhance the thermal conductivity of polymer blends. Abstract : Boron nitride (BN) possesses excellent thermal conductivity and remarkable insulating properties. However, poor compatibility between BN fillers and a polymer matrix and the weak ultimate mechanical properties of polymer composites are still big challenges to industrial applications in the thermal conductive field. In this paper, the dispersion of BN in a polystyrene (PS) matrix can be improved through the surface modification of BN by introducing in situ dispersion of polystyrene. Subsequently, the selective localization of modified BN in the PS phase can be realized. A co-continuous structure of polymer blends is designed to enhance the thermal conductivity of PS by introducing another polypropylene (PP) phase. The co-continuous PS/PP (60/40, w/w) phases can benefit further enhancement of thermal conductivity of PS due to the selective localization of modified BN in the PS phase. Furthermore, the thermal conductivity of PS/PP blends with only 14.5 wt%-modified BN is 2 times higher than that of neat PP and 30% higher than that of PP/BN.